A Powerful Diagnostic Tool (Eliciting) of the Teacher in Classroom Management (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The reason why eliciting should be carefully utilized by teachers is revealed in this article. Before starting the main topic, the teacher checks what the students have already been aware with by eliciting ideas, grammar structures, vocabulary. This article includes several effective tips to elicit the ideas successfully, which will really help the teacher to make the lesson more student-centered.